(untitled) (Al-Aasar, 2025)
This study explores the trends and research methodologies employed by female biographers in the field of Islamic biography (Sīrah). Over the years, female scholars have made significant contributions to the study of the life of Prophet Muhammad (PBUH), offering unique perspectives shaped by their social, cultural, and intellectual backgrounds. By analyzing selected works of prominent female Sīrah writers, this research highlights their thematic preferences, narrative styles, and methodological approaches. The study also examines how these authors address various aspects of the Prophet’s life, including his personal character, family relations, and societal contributions. Additionally, it assesses the extent to which gender-based experiences influence their interpretative frameworks and analytical perspectives. Through a comparative lens, the research contrasts the approaches of female biographers with their male counterparts, shedding light on the distinctive contributions of women in Sīrah literature. This study underscores the importance of recognizing and promoting female scholarship in Islamic historical and biographical studies. The findings suggest that the diverse perspectives of female biographers offer a more comprehensive understanding of the Prophet’s life and contribute to the richness of Islamic historiography.